Implementation of the Laong Pantar Model in Village Government Implementation in Sumbawa Regency - Sofyan HARYADI; Titi WIDANINGSIH; Nafiah ARIANI; Kholil KHOLIl (PT Keberlanjutan Strategis Indonesia, 2025)
The high intensity of formal communication, Laong Pantar communication between village political elites, the community results in a decrease in trust. A high level of uncertainty in a relationship causes a decrease in the level of intimacy of the communication content, resulting in a high level of reciprocity (feedback). (West & Turner: 2013: 150). Someone feels uncomfortable in a relationship because they feel they are not part of the group members Gudykunts and Kim (2003). Trying to find a way out to develop a new concept or communication model. How to apply the Laong Pantar model in the implementation of village government in Sumbawa district. What are the motives for understanding and disagreement within the village political elite and the community regarding the discourse of implementing Laong Pantar. Which is more dominant between santripetal motives and santrifugal motives within the political elite and the community regarding the discourse of implementing Laong Pantar in the implementation of village government. This type of research is descriptive qualitative, natural observation, Data collection uses observation, in-depth interviews, structured interviews and documentation. The results of the study show that the Laong Pantar implementation model desired by the political elite and the community is the elaborative final communication model. The motives for disagreement among political elites are habitual or accustomed to formal communication. This is due to a decline in trust in one's own culture, along with increased workload and political motives.